Spectral manipulation and complementary spectra with birefringence polarization control. (25th January 2017) - Ding, Pan-Feng; Han, Pin
Abstract: A polarization control method using crystal birefringence is suggested to manipulate polychromatic light. This scheme can be used with narrower bandwidth to produce various spectral effects, such as a notch filter, a flat top, and triangle-type, nipple-type, and central-frequency-dominant distributions. A modulated spectrum with greater bandwidth can be used as an optical frequency ruler, and phenomena called complementary spectra are also proposed, where the two spectral distributions, produced by rotating the polarizer, complement each other in the sense that the peaks and valleys in one spectrum are the reverse in the other. These results benefit the controlling of the spectral shape and the measurement of an unknown optical frequency.